AI-Centric Data Analytics in Public Behavioral Health Care - Thomas, Raphael Shobi Andhikad (International Journal of Computing and Engineering, 2025)
Artificial intelligence-driven data intelligence represents a paradigm shift in public behavioral health care, offering unprecedented capabilities to extract meaningful insights from complex datasets. This integration transforms the delivery of mental health services by enabling personalized interventions, early risk detection, and optimized resource allocation across populations. The convergence of electronic health records, social determinants data, behavioral metrics, and wearable device inputs creates a comprehensive foundation for enhanced clinical decision-making. Through advanced pattern recognition, natural language processing, and predictive modeling, these technologies facilitate the identification of at-risk individuals before crisis points, address service gaps in underserved communities, and generate evidence-based treatment recommendations. While implementation faces challenges including data privacy concerns, potential algorithmic bias, system interoperability barriers, and stakeholder acceptance, the benefits for population-level mental health outcomes are substantial. This transformative method promises to enhance access to quality behavioral healthcare, improve treatment efficacy, and reduce disparities through data-driven insights that guide both clinical practice and public health policy.